Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae) - Azevedo, Celso O.; Vargas, Juan M. R.; Colombo, Wesley D. (Zootaxa, 2020)
We provide a synopsis of the genus Discleroderma, which is known only from females. The genus is easily recognized by having tubercles on metasomal tergites III-V. In this synopsis we recognized D. gundari Terayama, D. indiensis Lanes & Azevedo, D. tuberculatum Magretti, and D. yemenensis Lanes & Azevedo as valid species. Additionally we discovered four more species D. concursum sp. nov., D. dolium sp. nov., D. plymouthoides sp. nov., and D. guamensis sp. nov., which are described and illustrated. We also provide an emended diagnosis and a key to the world species of this genus.